FSI modeling on the effect of artery-aneurysm thickness and coil embolization in patient cases. (July 2021) - Paz, C.; Suárez, E.; Cabarcos, A.; Pinto, S.I.S.
Highlights: The proposed methodology is a step forward to quantify the aneurysm rupture risk reduction. UDFs of ANSYS® software were used to implement the FSI hemodynamic model. The numerical model was validated using numerical research data of the literature. Results were obtained for different artery-aneurysm thickness combinations. After coil embolization process, the deformation and stress reduction are around 50 and 70%. Abstract: Background and objective: The attainment of a methodology to simulate the hemodynamic in patient-specific cerebral vessels with aneurysms is still a challenge. The novelty of this work is focused on the effect of coil embolization in a realistic cerebral aneurysm, according to the vessel wall thickness and aneurysm thickness, through transient FSI simulations. Methods: The quality of the mesh for simulations was checked with a specific mesh convergence study; and the numerical methodology was validated using numerical research data of the literature. The model was implemented in ANSYS® software. The total deformation and equivalent stress evolution in the studied cases, before and after coil embolization, were compared. More than 20 different models were employed due to different arterial wall thickness and aneurysm wall thickness combinations. Results: The obtained results have showed that deformation and stress values are highly influenced with the sac thickness. The thinner sac aneurysm thickness is, the greater deformation and stress are. The results after coil embolization process have highlighted that considering typical values of arterial wall thickness and aneurysm thickness 0.3 mm and 0.15 mm respectively, a deformation reduction around 50% and a stress reduction around 70% can be achieved. Conclusions: The proposed methodology is a step forward in the personalized medicine, quantifying the aneurysm rupture risk reduction, and helping the medical team in the preoperative planning, or to deciding the optimal treatment.